Fungsi Tuas Stamen dalam Penyerbukan dan Potensi Bunga Salvia sebagai Tanaman Hias di Kebun Raya Cibodas - , Sudarmono; , Destri (Jurnal Hortikultura Indonesia, 2013)
ABSTRACTStaminodes  or  sterile  stamen  of  S.   splendens  Wied  Sellow  ex-Neuw and S. ianthina   Otto  &  Dietr. ( Lamiaceae)  significantly  affected  the pollination process  of  the  species.  Sterile  stamen  is  directly  and closely related to insects  or pollinator and in  directly related in the process of evolution of S. splendens and S. ianthina. Following the assumption  that  the  evolutionary process on members of Lamiaceae based on the structure of  the flowers, the sterile  stamens  on the flowers  S.  splendens  and S. ianthina   plays  an important role in  attaching the pollen grains  on the body of pollinators. Pollinator interactions  to  a floweris significant on the  pollination  system. Sterile  stamens  was the lever  mechanism tested  in   field research , experimentalbiomechanics and pollination simulation, and the result  was seed production lower of  S. splendens (55% ± 6.4%) and S. ianthina  (25% ± 10.6%) when without staminodes than control of S. splendens (70% ± 4.2%) and  S.  ianthina  (35%  ±  9.2%).  The  beauty  of  the  flowers   that  are  commonly  found  in   members  of  theLamiaceae is the  potential of  S.  splendens and S.  ianthina.Key words:  Cibodas Botanic Garden, pollinators, S. ianthina ,  S.  splendens, stamens.ABSTRAKStaminoda  atau  tangkai   benang  sari   (stamen)   steril   pada  S.   splendens  Wied  Sellow ex- Neuwdan  S.  ianthina  Otto  &  Dietr.  (Lamiaceae) berpengaruh nyata pada  proses  penyerbukannya.  Stamen steril secara langsung berkaitan erat dengan serangga atau penyerbuk dan secara tidak langsung terhadap proses evolusi  pada  S.   splendens  dan  S. ianthina.  Diasumsikan  bahwa  proses   evolusi  pada  anggota Lamiaceaedidasarkan  pada  struktur  bunga,  stamen  steril  pada  bunga  S.   splendens  dan  S.  ianthina   yang  mana memainkan peranan penting pada penempelan butir sari pada tubuh penyerbuk. Penyerbuk berinteraksi pada suatu bunga secara nyata dalam sistem penyerbukan. Stamen steril diuji mekanisme tuasnya pada percobaan lapangan,   percobaan biomekanik dan simulasi penyerbukan, dan hasilnya adalah produksi biji rendah padaS.  splendens  ( 55%  ±  6. 4%)  dan  S.  ianthina  25%  ±  10. 6%)  ketika  tanpa  staminoda daripada  perlakuan kontrol  pada  S.  splendens  (70%  ±  4. 2%  dan  S. ianthina   35%  ±  9. 2%).  Keindahan  bunga  yang  umum ditemukan pada anggota Lamiaceae merupakan potensi pada S. splendens  dan S. ianthina .Kata kunci: Kebun Raya Cibodas, penyerbuk, S. ianthina,  S.  splendens, stamen